Pregravid Weight Gain Is Associated with an Increased Risk of Gestational Diabetes - Sunmie Kim; Kyungdo Han; Su-Yeon Choi; Min Joo Kim; Sun Young Yang; Seung Ho Choi; Jeong Yoon Yim; Jin Ju Kim; Min-Jeong Kim (Diabetes & Metabolism Journal)
Background Studies have reported a significant association between pregravid weight gain and the subsequent development of gestational diabetes mellitus (GDM) in various populations. The current study aims to investigate this relationship using data from the Korean National Health Insurance Service database. Methods We conducted a retrospective nationwide population-based cohort study, involving 159,798 women who gave birth between 2015 and 2017 and had undergone two national health screening examinations: 1 year (index checkup) and 3 years before (baseline checkup) their respective estimated conception date. Participants were categorized into five groups based on the extent of weight change between the two examinations: more than 10%, 5% to 10%, –5% to 5% (reference group), –10% to –5%, and more than –10%. The study assessed the association between pregravid weight change and GDM risk. Results Among the 146,363 women analyzed, 11,012 (7.52%) were diagnosed with GDM. Multiple regression analysis revealed that women who gained 5% to 10% of their weight had a 12% increased risk of GDM (adjusted odds ratio [aOR], 1.12; 95% confidence interval [CI], 1.06 to 1.17), while those who gained ≥10% had a 34% higher risk (aOR, 1.34; 95% CI, 1.26 to 1.43). Notably, pregravid weight gain was particularly associated with GDM risk in non-obese or non-metabolic syndrome groups at index checkup. Conclusion Pregravid weight gain showed a dose-dependent association with a higher risk of GDM. This association was more pronounced in non-obese individuals emphasizing the importance of minimizing pregravid weight gain for GDM prevention, even in non-obese women.